(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Non-compliance to manufactures recommended replacement frequency is expected to result in ocular complications. While many reports the percentage of people who are non- compliant, only some report pay attention to the care and maintenance instructions that eye care practitioners provide to their patients. The goal of this study is to draw attention to the instructions imparted by eye care practitioner to their user and explore the measure taken by them to reduce contact lens non-compliance. Method: Eye care practitioner from Mumbai who were willing to provide consent and share their experience participated in this anonymous online survey which was designed with the help of focused group discussion with a panel of experts. Results: Majority of eye care practitioner had 5 years or more clinical experience in the field of contact lens. About 81% contact lens users in their practice were between the age of 20-29 years. These eye care practitioners believed their contact lens user non-compliant to replacement schedule of contact lens, was 35% due to forgetting the actual day of replacement, 46% as they forget to reorder their lenses, 33% believe to do this to save money, 41% believe contact lens user have lack of time and 36% believe they don’t change their lenses as there is no discomfort in continuing. Of all 55% of eye care practitioner agree in giving written information, SMS or telephonic reminder and agreed that increase in follow up would improve compliance. However, 57% of eye care practitioner strongly agree that contact lens practice should be restricted to Eye care practitioner only to increase compliance in contact lens users. Conclusion: Reminders to follow up and to buy contact lens as per their previous purchase can help in reducing majority of non-compliance to replacement schedule. In addition, eye care practitioner strongly agrees to restrict contact lens practice to Eye care practitioner only.